2018
DOI: 10.1186/s12863-018-0656-1
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping for resistance to and tolerance for the rice root-knot nematode, Meloidogyne graminicola

Abstract: BackgroundThe root-knot nematode Meloidogyne graminicola is an obligate biotrophic pathogen considered to be the most damaging nematode species that causes significant yield losses to upland and rainfed lowland rice production in South and Southeast Asia. Mapping and identification of quantitative trait loci (QTL) for resistance to and tolerance for M. graminicola may offer a safe and economic management option to farmers. In this study, resistance to and tolerance for M. graminicola in Asian rice (Oryza sativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 42 publications
0
25
1
Order By: Relevance
“…Both QTL-seq experiments revealed segregation from 23 Mb to the bottom of chromosome 11. This locus does not seem to be close to previously detected QTLs for nematode resistance on chromosome 11 from Shrestha et al ( 2007 ) or Galeng-Lawilao et al ( 2018 ). Within this region there are 859 annotated genes (according to the Rice Genome Annotation Project) including 88 (annotated as) transposons and 167 retrotransposons, 231 “expressed protein” and 29 hypothetical genes.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Both QTL-seq experiments revealed segregation from 23 Mb to the bottom of chromosome 11. This locus does not seem to be close to previously detected QTLs for nematode resistance on chromosome 11 from Shrestha et al ( 2007 ) or Galeng-Lawilao et al ( 2018 ). Within this region there are 859 annotated genes (according to the Rice Genome Annotation Project) including 88 (annotated as) transposons and 167 retrotransposons, 231 “expressed protein” and 29 hypothetical genes.…”
Section: Discussioncontrasting
confidence: 63%
“…More recently, Phan et al ( 2018 ) reported a Hypersensitivity-Like Reaction (HR) to M. graminicola infection in the Asian rice cultivar Zhonghua 11 suggesting this resistance to M. graminicola to be qualitative rather than quantitative involving (a) major gene(s). Galeng-Lawilao et al ( 2018 ) have reported main effect QTLs for field resistance in Asian rice on chromosomes 4, 7 and 9 plus two epistatic interactions (between loci on chromosome 3 and 11, and between 4 and 8).…”
Section: Introductionmentioning
confidence: 99%
“…However, the yield of rice is substantially afflicted by several biotrophic pathogens including rice root-knot nematode (RRKN), Meloidogyne graminicola. This sedentary endoparasite occurs in a wide range of rice-based production systems in South and Southeast Asia, including lowland, upland, rainfed, irrigated, deep-water as well as aerobic rice, and causes economic yield loss of rice [2][3][4][5][6][7]. In the vascular bundle, near the root tip, RRKN induces a feeding site (3-5 giant cells) that serves as the permanent nutrient sink for the nematode.…”
Section: Introductionmentioning
confidence: 99%
“…In order to mitigate the loss by RRKN in rice, use of chemical nematicides, crop rotation (with mung bean, mustard and sesame as poor hosts) and continuous flooding are the recommended practices [3,6,7]. Although prolonged flooding may reduce the RRKN populations by inhibiting the second-stage juveniles (J2) to invade rice roots, increasing scarcity of water for agricultural use may render this practice impractical to adopt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation